Enhanced Interactive Interior Spaces for Safe Design in Administrative Office Buildings (Al-Academy, 2025)
Safe design is not limited to physical protection such as fire resistance or security against theft, but rather extends to include psychological safety and the general well-being of workers. Interactive interior spaces become effective tools for enhancing safety, by providing smart solutions that contribute to improving the quality of life within work environments. These spaces can include smart lighting systems that adapt to natural light levels to reduce eye strain, or ventilation systems that respond to indoor air quality to provide a safe and healthy environment. Spaces provide unprecedented opportunities for interaction between users and the space itself, enhancing the sense of control and comfort to work towards a safe work environment with safety features. The research entitled: "Interactive interior spaces that enhance safe design in administrative offices" and the research problem was represented by the following question: "What are the methods of interactive technologies used in designing private interior spaces for administrative office buildings?" The research aims to use technologies and smart design to enhance safety and protection in work environments and employ smart entry systems and sensors and provide lighting that leads to improving the quality of space, in addition to a flexible and intelligent design for buildings that allows easy access control. The theoretical framework calls for two topics, the first of which includes: interactive interior design, while the second topic is safe design in interactive space.The research adopted the descriptive method in the analysis process (3) interactive administrative offices that represent models of research samples that were intentionally chosen from the original research community that represents interactive interior spaces that enhance safe design in administrative offices in the Asian countries' region.The study resulted in a set of conclusions, including:1- The interactive interior space is a new type of space capable of accommodating different functions and adapting to the requirements of the era and is mobile and adjustable to provide a comfortable interior environment that responds to the requirements of the era.2- The interactive design is represented by a set of specific tools that function as a link between the determinants of the interior space and its modern technologies that interact with the user through sensors and computing everywhere to achieve a safe work environment and to provide safety and security requirements within the spaces.Interactive spaces in administrative offices work to integrate modern technologies with their contemporary technologies with the traditional work environment to enhance interaction and productivity. The expected benefits of employing them include increased collaboration among employees, improved communication processes, enhanced creativity and innovation, and a safer, more dynamic work environment that is more suited to modern business needs